Urgent care for patients with dementia: a scoping review of associated factors and stakeholder experiences - Rebecca Barnes; Penny Xanthopoulou; Jemima Dooley; Matthew Booker (BMJ Open)
Objectives People with dementia are more vulnerable to complications in urgent health situations due to older age, increased comorbidity, higher dependency on others and cognitive impairment. This review explored the factors associated with urgent care use in dementia and the experiences of people with dementia, informal carers and professionals.Design Scoping review. The search strategy and data synthesis were informed by people with dementia and carers.Data sources Searches of CINAHL, Embase, Medline, PsycINFO, PubMed were conducted alongside handsearches of relevant journals and the grey literature through 15 January 2019.Eligibility criteria Empirical studies including all research designs, and other published literature exploring factors associated with urgent care use in prehospital and emergency room settings for people with dementia were included. Two authors independently screened studies for inclusion.Data extraction and synthesis Data were extracted using charting techniques and findings were synthesised according to content and themes.Results Of 2967 records identified, 54 studies were included in the review. Specific factors that influenced use of urgent care included: (1) common age-related conditions occurring alongside dementia, (2) dementia as a diagnosis increasing or decreasing urgent care use, (3) informal and professional carers, (4) patient characteristics such as older age or behavioural symptoms and (5) the presence or absence of community support services. Included studies reported three crucial components of urgent care situations: (1) knowledge of the patient and dementia as a condition, (2) inadequate non-emergency health and social care support and (3) informal carer education and stress.Conclusions The scoping review highlighted a wider variety of sometimes competing factors that were associated with urgent care situations. Improved and increased community support for non-urgent situations, such as integrated care, caregiver education and dementia specialists, will both mitigate avoidable urgent care use and improve the experience of those in crisis.